Increased expression of the WNT antagonist sFRP-1 in glaucoma elevates intraocular pressure - Wang, Wan-Heng (American Society for Clinical Investigation, 2008)
Elevated intraocular pressure (IOP) is the principal risk factor for glaucoma and results from excessive impedance of the fluid outflow from the eye. This abnormality likely originates from outflow pathway tissues such as the trabecular meshwork (TM), but the associated molecular etiology is poorly understood. We discovered what we believe to be a novel role for secreted frizzled-related protein-1 (sFRP-1), an antagonist of Wnt signaling, in regulating IOP. sFRP1 was overexpressed in human glaucomatous TM cells. Genes involved in the Wnt signaling pathway were expressed in cultured TM cells and human TM tissues. Addition of recombinant sFRP-1 to ex vivo perfusion-cultured human eyes decreased outflow facility, concomitant with reduced levels of β-catenin, the Wnt signaling mediator, in the TM. Intravitreal injection of an adenoviral vector encoding sFRP1 in mice produced a titer-dependent increase in IOP. Five days after vector injection, IOP increased 2 fold, which was significantly reduced by topical ocular administration of an inhibitor of a downstream suppressor of Wnt signaling. Thus, these data indicate that increased expression of sFRP1 in the TM appears to be responsible for elevated IOP in glaucoma and restoring Wnt signaling in the TM may be a novel disease intervention strategy for treating glaucoma.